Investigating Characteristics of Award-Winning Grades 7-12 Mathematics Teachers from the Shandong Province in China - Su Liang; Sarah Glaz; Thomas DeFranco (Arizona State University, 2012)
International comparison studies indicate that Chinese students outperform many of their peers in mathematics tests and competitions. Since teaching is a major determinant in students' learning gains, it is reasonable to hypothesize that this learning gap is associated with their teachers. The development of teaching expertise has not received sufficient attention in research investigations in mathematics education. By examining a group of award-winning grades 7-12 mathematics teachers from the Shandong province in China, this study identified the characteristics of these teachers and illuminated how their expertise had been developed over the years. The findings provide an insightful view of effective teaching practices in China from an international perspective.